2017
DOI: 10.1002/term.2439
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired solute enables preservation of human oocytes using minimum volume vitrification

Abstract: The ability to cryopreserve human oocytes has significant potential for fertility preservation.Current cryopreservation methods still suffer from the use of conventional cryoprotectants, such as dimethyl sulphoxide (DMSO), causing loss of viability and function. Such injuries result from the toxicity and high concentration of cryoprotectants, as well as mechanical damage of cells due to ice crystal formation during the cooling and rewarming processes. Here we report the preservation of human oocytes following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Most importantly, injection of the stem cell-derived AMHR2+ enriched cell population into subfertile mice exposed to gonadotoxic chemotherapy restores ovarian function as indicated by both the recovery of steroidogenic production and de novo generation of stem-cell derived gametes. Finally, we show that these stem cells can trigger activation of the endogenous oogenesis process to produce functionally mature oocytes as demonstrated by their capacity for fertilization and activation via a calcium ionophore towards the generation of parthenotes 21 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most importantly, injection of the stem cell-derived AMHR2+ enriched cell population into subfertile mice exposed to gonadotoxic chemotherapy restores ovarian function as indicated by both the recovery of steroidogenic production and de novo generation of stem-cell derived gametes. Finally, we show that these stem cells can trigger activation of the endogenous oogenesis process to produce functionally mature oocytes as demonstrated by their capacity for fertilization and activation via a calcium ionophore towards the generation of parthenotes 21 .…”
Section: Introductionmentioning
confidence: 90%
“…The addition of 5% human follicular fluid (HFF) to culture media enhances E2 synthesis in mGriPSCs (V; n=3, Mann-Whitney U test, P<0.05). 1% and 5% HFF in media also promotes increased expression of an oocyte marker ZP1 (zona pellucida 1) and a granulosa cell marker GJA1 21 (gap junction protein alpha) according to ICC positive cell counts (VI; n=7, Mann-Whitney U test, p<0.003). Scale bars in I. D-O, 25 μm; in II.…”
Section: Stem Cell-derived Ovarian Tissue Retains Endocrine Function mentioning
confidence: 99%
“…Researchers have resorted to investigating other potential cryoprotectants like ectoine [ 77 ] since the use of conventional cryoprotectants like DMSO and glycerol is clouded with concerns of toxicity, and loss of viability [ 77 ]. Bearing the good prospects of AFP use in mind, continuous research in this direction will avoid setbacks like that observed in the cryopreservation of bovine oocyte cryopreservation with AFP III [ 78 ] where mitotic spindle integrity was not preserved and they might just be the solution to clinically applicable oocytes and embryo cryopreservation [ 79 ].…”
Section: Applications Of Afps In Cryopreservationmentioning
confidence: 99%
“…The deterioration effects posed due to exposure of cells to conventional cryoprotectants can be avoided by replacing them with nontoxic bioinspired cryoprotectants. Recently, bioinspired biocompatible materials, such as ectoine and trehalose, have been utilized to cryopreserve human cells (e.g., red blood cells, oocytes, and stem cells) …”
mentioning
confidence: 99%